2021
DOI: 10.1002/ejic.202100651
|View full text |Cite
|
Sign up to set email alerts
|

[(Me6TREN)MgOCHPh2][B(C6F5)4]: A Model Complex to Explore the Catalytic Activity of Magnesium Alkoxides in Ketone Hydroboration

Abstract: The sterically hindered monomeric alkoxomagnesium compound [(Me 6 TREN)MgOCHPh 2 ][B(C 6 F 5 ) 4 ] (1) has been used to explore the role of magnesium alkoxides in ketone hydroboration. Experiments and DFT calculations are suggestive of a concerted reaction pathway traversing through a six-membered transition state involving MgÀ OCHPh 2 , BÀ H, and C=O bonds. Prompted by this hypothesis, we investigated the activity of [Mg(OCHPh 2 ) 2 ] (3), which exhibits turn-over frequency reaching up to 59,400 h À 1 under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(32 reference statements)
0
5
0
Order By: Relevance
“… , This mechanism was mainly substantiated by computational studies as only a limited amount of experimental evidence was reported. However, both computational and experimental observations suggested that the metathesis step might not have been feasible under the described reaction conditions and that the central atom (i.e., boron) might not have been directly involved in the overall reduction process. In fact, for the hydroboration of polarized unsaturated bonds, the formation of four-coordinate B–H containing compound(s) (e.g., A , Scheme ), either through decomposition/redistribution or activation/binding by a nucleophile (e.g., the Clark mechanism; path 2, Scheme ), was postulated to represent a key initiator responsible for the generation of catalytically active species B in the overall mechanism. ,, This was further supported by the fact that [HBPh 3 ] − (0.001 mol % as a Me 6 -TREN-Li salt) was identified as one of the most efficient (pre)­catalytic systems for reduction of various carbonyl compounds at room temperature . Moreover, the fact that simple (in)­organic salts (e.g., NaOH, n BuLi, NaH, KF, etc.)…”
Section: Introductionmentioning
confidence: 99%
“… , This mechanism was mainly substantiated by computational studies as only a limited amount of experimental evidence was reported. However, both computational and experimental observations suggested that the metathesis step might not have been feasible under the described reaction conditions and that the central atom (i.e., boron) might not have been directly involved in the overall reduction process. In fact, for the hydroboration of polarized unsaturated bonds, the formation of four-coordinate B–H containing compound(s) (e.g., A , Scheme ), either through decomposition/redistribution or activation/binding by a nucleophile (e.g., the Clark mechanism; path 2, Scheme ), was postulated to represent a key initiator responsible for the generation of catalytically active species B in the overall mechanism. ,, This was further supported by the fact that [HBPh 3 ] − (0.001 mol % as a Me 6 -TREN-Li salt) was identified as one of the most efficient (pre)­catalytic systems for reduction of various carbonyl compounds at room temperature . Moreover, the fact that simple (in)­organic salts (e.g., NaOH, n BuLi, NaH, KF, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is a redox-inactive alkaline earth metal and has been remarkably applied to stoichiometric reactions in the form of Grignard reagents for more than a century. Due to its low cost and environmentally benign nature, magnesium as catalytic reagents has also witnessed remarkable advances in hydroboration of unsaturated bonds, alkene hydroamination/hydrogenation, dehydrocoupling reactions, and others . Compared with these well-established transformations, the magnesium catalysis toward alkene hydrophosphinylation remains largely lagged behind.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted here that there are literature precedents for magnesium catalyzed reactions, where the mechanism does not involve a magnesium hydride intermediate. [29][30][31] In summary, we have identified a convenient approach to the synthesis of formamide derivatives from the widely available isocyanates by employing our previously reported bis(phosphino)carbazolido-magnesium methyl complex as a catalyst. Our report represents the first example of an alkaline earth metal catalyst that controls the reduction of isocyanates Table 2 The efficiency of the catalytic cycle for the reaction mechanism investigated has been calculated with the AUTOF program by employing the ''Energetic Span Model'' (ESM) 32 Mechanistic pathways TOF (h À1 ) Fig.…”
mentioning
confidence: 99%
“…It must be noted here that there are literature precedents for magnesium catalyzed reactions, where the mechanism does not involve a magnesium hydride intermediate. 29–31…”
mentioning
confidence: 99%